2016
DOI: 10.1002/joc.4895
|View full text |Cite
|
Sign up to set email alerts
|

Temperature extremes in the Argentina central region and their monthly relationship with the mean circulation and ENSO phases

Abstract: The aim of this study is to analyse the interannual variability of monthly climatic indices of extreme daily temperature in the central-north region of Argentina throughout a year and its relationship with the atmospheric circulation. The impact of El Niño-Southern Oscillation (ENSO) over different temperature indices throughout the year is specially analysed. Globally used indices in the 1970-2010 period are utilized for this purpose. The trends of temperature extremes show warming conditions in several month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 25 publications
4
19
0
4
Order By: Relevance
“…5d shows that the minimum temperature is related to the ENSO mode with a periodicity close to 3 years, with warmer Tmn during El Niño years and cooler Tmn during La Niña events. These results are consistent with Müller et al (2000) and Rusticucci et al (2017), who reported that El Niño events intensify warm spells and reduce the number of climatological freezing days while La Niña events increase cold events. Figure 6a and b show the leading pattern of decadal-tomultidecadal precipitation variability.…”
Section: Interannual Modessupporting
confidence: 92%
“…5d shows that the minimum temperature is related to the ENSO mode with a periodicity close to 3 years, with warmer Tmn during El Niño years and cooler Tmn during La Niña events. These results are consistent with Müller et al (2000) and Rusticucci et al (2017), who reported that El Niño events intensify warm spells and reduce the number of climatological freezing days while La Niña events increase cold events. Figure 6a and b show the leading pattern of decadal-tomultidecadal precipitation variability.…”
Section: Interannual Modessupporting
confidence: 92%
“…5d) with warmer Tmn during El Niño years and cooler Tmn during La Niña events. These results are consistent with Müller et al (2000) and Rusticucci et al (2017) who reported that El Niño events intensify warm spells and reduce the number of climatological freezing days while La Niña events increase cold events. 10 Hydrol.…”
Section: Interannual Modessupporting
confidence: 92%
“…Accordingly, there is a global demand for understanding and characterizing HW events, considering the associated social, economic, and environmental impacts. However, the widespread interest in characterizing the occurrence of extreme temperatures in various continents has not attained the same level in South America and particularly in Brazil, despite few exceptions (Cerne and Vera, 2011;Renom et al, 2011;Rusticucci, 2012;Hannart et al, 2015;Bitencourt et al, 2016;Ceccherini et al, 2016;Rusticucci et al, 2016Rusticucci et al, , 2017. Nevertheless, South America and Brazil, in particular, are no exception to the global positive trend of surface temperature in the last decades (Vincent et al, 2005;Alexander et al, 2006;Skansi et al, 2013;Soares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%